CLIMATE CHANGE AND TREND OF RAINFALL IN THE SOUTH-EAST PART OF COASTAL BANGLADESH - Zaheed Hasan; Sabiha Akhter; Mamunul Islam (European Scientific Journal, ESJ, 2014)
Rainfall has been widely considered as one of the starting point towards the apprehension of climate change courses. Various studies have indicated due to climate change rainfall pattern in Bangladesh is most likely to change which would have adverse impacts on lives and livelihoods of millions of people. This study investigates temporal variability of precipitation of the south-east coast of Bangladesh over the period of 1949- 2011. The Mann-Kendall test and the Sen’s slope estimators have been used to detect rainfall trends and to understand magnitude of changes. We find that after 1990 mean annual rainfall has increased significantly in the south east part of Bangladesh compare to the period between 1949 and 1989. The rate of increase is 10% that is 463 mm/year. However, this pattern of increase in rainfall is not evenly distributed among all the four seasons. Sixty three years (1949-2011) trend analysis shows that rainfall has increased significantly during pre-monsoon season. The rate of increase in rainfall during pre-monsoon season is 3 mm/year. Trend analysis of rainfall for the last two decades (1990-2011) reveals a bit different trend. It shows increasing trend of rainfall in monsoon season and decreasing trend of rainfall in pre monsoon and post monsoon season. Although these trends are not statistically significant. Sen’s test reveals rainfall during monsoon is increasing at the rate of 10 mm/year.